2013
DOI: 10.3747/pdi.2013.00017
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Requirements for an Urgent-Start Peritoneal Dialysis Program

Abstract: Patients with advanced chronic kidney disease nearing dialysis but without pre-established access almost uniformly initiate dialysis with a temporary central venous catheter. These catheters are associated with high rates of infection and flow disturbances, requiring removal and subsequent replacement. Many of these patients might be candidates for peritoneal dialysis (PD), but because of the absence of prior catheter placement, the default initial modality is hemodialysis. Recent reports, however, have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 18 publications
0
52
0
1
Order By: Relevance
“…18 PD has been seen as a viable and safe alternative to HD in unplanned dialysis starts in developed and developing nations, nurturing the growth of PD programs. 19,20,21,22,23 Casaretto et al 24 and Ghaffari et al 25 reported that urgent-start PD programs call for novel infrastructure and specific care processes. The medical team has to be ready and available to implant peritoneal catheters in emergency settings, with the active participation of nephrologists.…”
Section: Introductionmentioning
confidence: 99%
“…18 PD has been seen as a viable and safe alternative to HD in unplanned dialysis starts in developed and developing nations, nurturing the growth of PD programs. 19,20,21,22,23 Casaretto et al 24 and Ghaffari et al 25 reported that urgent-start PD programs call for novel infrastructure and specific care processes. The medical team has to be ready and available to implant peritoneal catheters in emergency settings, with the active participation of nephrologists.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the first phase of the process of urgent start PD is to ensure that the hospital or facility has the support of experienced and dedicated dialysis educators for patients and their families to ensure that the right decision is made for urgent PD start with a view of continued long-term PD. The next phases, including PD catheter insertion and the practical implementation of an urgent start PD program, are beyond the scope of this discussion but are reviewed elsewhere (19)(20)(21).…”
Section: Discussion Of Question 1bmentioning
confidence: 99%
“…Most of patients do not need intensive PD (high volume), so intermittent PD may suffice. The ability to start PD urgently requires expedited options education, urgent catheter placement, unique changes in the PD unit infrastructure, nursing support (training and staffing), hospital and dialysis unit administrative support, and protocol‐driven orders …”
mentioning
confidence: 99%
“…15,16 In the United States and Canada, interest has also recently been renewed in the more urgent initiation of PD to avoid temporary vascular access catheters in patients who are referred late to a nephrologist. [12][13][14][15][16][17][18][19][20] There have been no such studies performed in developing countries.…”
mentioning
confidence: 99%